Overcoming Crisis Opportunity: Thai Durian Producers’ Adaptation in a Transitional Era - Tana, Supasit; Rattanaprathum, Nopparat; Wattanachaiyingcharoen, Det; Chankun, Arom (Journal of Social Sciences Naresuan University, 2026)
Thailand is the world’s leading producer and exporter of durians, generating income of over 100 billion baht for farmers and entrepreneurs. However, the growing demand for durian products has intensified market competition, while climate variability has made the production process increasingly difficult. This study aims to analyze the problems and challenges in durian production in Thailand and propose adaptation strategies for farmers and entrepreneurs. A quantitative research method was employed, using descriptive statistics to analyze data collected from 580 farmers and 52 government officials through questionnaires. The results revealed that, for farmers, the top three problems and challenges were: (1) rising production costs (x̄ = 2.86, moderate level), (2) emerging plant diseases and pests (x̄ = 2.64, moderate level), and (3) drought and water shortages for cultivation (x̄ = 2.41, low level). For entrepreneurs, the top three issues were: (1) market monopoly by China (x̄ = 3.12, moderate level), (2) fraudulent use of GMP certificates (x̄ = 2.88, moderate level), and (3) illegal importation and re-export of foreign durians (x̄ = 2.79, moderate level). The synthesis of adaptation strategies suggests that farmers should reduce production costs by using bio-fertilizers, strengthen disease monitoring through mobile applications and drones, and improve irrigation systems, such as drip irrigation, to address drought and water scarcity. For entrepreneurs, strategies include expanding export markets, developing retail systems to reduce dependency on China, and implementing a traceability system to prevent the fraudulent use of GMP certificates. In addition, entrepreneurs should adopt advanced technologies to verify the origin of durians. Recommendations are that farmers enhance their agricultural knowledge and digital technology skills, while entrepreneurs accelerate their adaptation to meet the challenges of competition and strict trade standards in the export market.